Successful Treatment with Empirical Erlotinib in a Patient with Respiratory Failure Caused by Extensive Lung Adenocarcinoma - Suk Hyeon Jeong (Korean Journal of Critical Care Medicine, 2016)
We herein describe a 70-year-old woman who presented with respiratory failure due to extensive lung adenocarcinoma. Despite advanced disease, care in the intensive care unit with ventilator support was performed because she was a newly diagnosed patient and was considered to have the potential to recover after cancer treatment. Because prompt control of the cancer was needed to treat the respiratory failure, empirical treatment with an oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor was initiated before confirmation of EGFR-mutant adenocarcinoma, and the patient was successfully treated. Later, EGFR-mutant adenocarcinoma was confirmed.